The Effect of Tax Service Quality, Tax Awareness Campaigns, and the Use of E-Tax Applications on the Tax Compliance of Local Taxpayers at the Malang City Revenue Agency - Putra, Fajar Fauzian Krishna; Wirshandono Y, Doni; Sari, Ati Retna (International Journal of Business, Law, and Education, 2026)
This study aims to analyze the influence of tax service quality, tax outreach, and the use of e-tax applications on local taxpayer compliance at the Regional Revenue Agency (Bapenda) of Malang City. This study employs a quantitative, survey-based approach. The study population consists of local taxpayers in Bandungrejosari Village, Malang City, and the sample size was determined using the Slovin formula and proportional random sampling, with 100 respondents. Data were collected via a questionnaire and analyzed using multiple linear regression. The results indicate that tax service quality, tax awareness campaigns, and the use of e-tax applications simultaneously have a significant effect on local taxpayer compliance. Partially, the quality of tax services and the use of e-tax applications have a positive and significant effect on taxpayer compliance, while tax socialization has no significant effect. This study concludes that an increase in taxpayer compliance is more influenced by service quality and the ease of the digital tax system.